Russian University Students about Distance Learning: Assessments and Opportunities - I. A. Aleshkovskiy; A. T. Gasparishvili; O. V. Krukhmaleva; N. P. Narbut; N. E. Savina (Moscow Polytechnic University, 2020)
The forced shift to remote learning in universities in March 2020 raised the complex issues of organizing lifelong learning for students, conducting academic assessments and maintaining the stability of the educational institution in general for educational systems of all countries of the world. This paper examines peculiarities and general problems of distance learning in the higher education system. It is based on the materials of the sociological survey "Opinions of Russian universities' students on the forced distance learning", conducted in May-June 2020. 31,423 university students in all federal subjects of Russia were interviewed. Analysis of research data covers the following areas: organizational problems of transition to distance learning; resources used, organization of lectures and seminars, assessment of the positive and negative aspects of distance learning; perspectives, limitations and trajectories of distance learning implementation in Russian universities.The article also provides comparative data on the analysis of the issues of distant learning of Russian and foreign researchers. The authors propose future-oriented measures for organizing distance learning in universities in the case of the introduction of quarantine restrictions, consider possible forms of combining distance and full-time education, the prospects for the introduction of digital technologies in the organization of training in universities.